Rural-urban Health Disparities for Cardiovascular Disease in the Republic of Kazakhstan - Mukasheva, Gulbarshyn; Bulegenov, Tolkyn; Kolyado, Vladimir; Kazyeva, Altynai (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: An important global public health problem in many economically developed countries, in particular Kazakhstan, is the leading cause of incidence of and mortality from cardiovascular disease (CVD). AIM: The purpose of our study was to compare incidence and mortality from CVD in urban and rural areas of the Republic of Kazakhstan in 2019 based on statistics. METHODS: We conducted a descriptive study, which based on secondary data from the statistical reports on the Republic of Kazakhstan «Health of the Republic of Kazakhstan and the activities of health care organizations». Information from this database were generated by 14 provinces, three cities of republican significance and whole Kazakhstan. In addition, these indicators were divided for rural and urban settlements. RESULTS: Data from our epidemiological study of the incidence of and mortality from cardiovascular disease (CVD) in all provinces indicate a relatively high incidence of and mortality from CVD among urban population of the Republic of Kazakhstan. Among urban residents (per 100,000 population), the highest incidence rates of CVD was in Akmola province (3771.7), the ischemic heart disease (IHD) was in Almaty city (850.8), arterial hypertension (AH) was in Akmola province (2623.8), acute myocardial infarction was in the North Kazakhstan province (212.9), the highest mortality from CVD was in Karaganda province (365), the IHD was in East Kazakhstan province (135.4). Among rural residents (per 100,000 population), there are high incidence rates of CVD in the East Kazakhstan province (3452.8), the IHD in Zhambyl province (713.1), AH in the East Kazakhstan province (1871.4), acute myocardial infarction in Atyrau province (148.3), the highest mortality from CVD was in East Kazakhstan province (201.9), and the IHD also in East Kazakhstan province (77.3). CONCLUSIONS: There is rural-urban health inequality in many countries and CVD is not the exclusion. In the Republic of Kazakhstan, the rural population has got lower rates of incidence and mortality. This may be due to the bad access to medical facilities that are typical for rural areas of Kazakhstan and the shortage of modern diagnostic equipment which may interfere with timely diagnosis.